The daily laws : 366 meditations on power, seduction, mastery, strategy, and human nature - Greene, Robert (Profile Books, 2021)
"From the #1 New York Times bestselling author, a year's worth of daily wisdom and guidance, distilled from the lessons of his six previous books and from never-before-published work Robert Greene, the bestselling author, philosopher, and life guide for millions of people, applies the wisdom of centuries to his mission of revealing the secret truths about the essential forces shaping our lives. His readers look to him to answer their most elemental question: "I want to become more powerful, stronger, more in control, the best at what I do. What's the secret to it?" The answer: Pick up The Daily Laws every single day. A beautifully designed volume that is perfect for bedside reading or gifting, The Daily Laws draws from Greene's body of work to offer a page of refined and concise wisdom for each day of the year, in an easy-to-digest lesson that will only take a few minutes to absorb. Each day will feature a Daily Law as well--a prescription or prompt for the reader to follow. Each month will center around a major theme: power, seduction, war, strategy, human nature, politics, productivity, mastery, psychology, leadership, adversity, or emotion. And each entry will be tagged to its source, so that readers who want to study the topic in more depth know where to look. "Daily study," Leo Tolstoy wrote in 1884, is "necessary for all people." More than just an entry point for new fans, this book will be a Rosetta stone for understanding and internalizing the many lessons that fill Greene's books, and will reward a lifetime of reading and re-reading"--